2011
DOI: 10.1002/pca.1361
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Sulphur metabolites in Arabidopsis thaliana via LC‐ESI‐MS/MS and 34S‐metabolic Labelling

Abstract: The validated method for determination of methionine, reduced glutathione and oxidised glutathione was effectively applied to measure metabolite dynamics of sulphur-containing metabolites at the whole-plant level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The cysteine autotrophy of plants allows labeling of sulfur‐containing metabolites by feeding of stable sulfur isotope anions (Giavalisco et al ., ; Hsieh et al ., ). In order to determine the degree of isotope labeling and to optimize the strategy for labeling sulfur‐containing compounds in Arabidopsis, seeds were germinated and seedlings were grown in the presence of various concentrations of 34 S‐sulfate.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The cysteine autotrophy of plants allows labeling of sulfur‐containing metabolites by feeding of stable sulfur isotope anions (Giavalisco et al ., ; Hsieh et al ., ). In order to determine the degree of isotope labeling and to optimize the strategy for labeling sulfur‐containing compounds in Arabidopsis, seeds were germinated and seedlings were grown in the presence of various concentrations of 34 S‐sulfate.…”
Section: Resultsmentioning
confidence: 97%
“…The reproducibility and comparability of the analysis are critical for identification of metabolites that are selectively enriched in samples by using an untargeted approach (Saito and Matsuda, ). Recently, 34 S labeling was introduced for metabolome analysis using online liquid chromatography and high‐resolution MS (Giavalisco et al ., ; Hsieh et al ., ). The studies identified sulfur‐containing metabolites in Arabidopsis based on the labeling‐specific isotopic pattern.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Perchloric acid was used to protect metabolites from enzymatic degradation [ 41 ], and to avoid sulfur metabolites oxidation and degradation [ 14 , 42 , 43 ] under basic and neutral condition. Formic acid was used for enhancing electrospray ionization.…”
Section: Methodsmentioning
confidence: 99%
“…e number of distinct proteins that can be identi ed from complex samples has been increased by the use of shotgun proteomics, a gel-free liquid chromatography tandem mass spectrometry (LC-MS/MS) analysis, compared to traditional gel-based approaches [36,46,[58][59][60]. However, there is no single standardized procedure for the analysis of all proteins and metabolites because these are highly diverse and biochemically heterogeneous [37].…”
Section: Proteomics Studiesmentioning
confidence: 99%